Seven esophageal perforation cases after aortic replacement/stenting for thoracic aortic dissection or aneurysm - Yoshihisa Yaguchi; Yoshimasa Kumata; Masahiro Horikawa; Takashi Kiyokawa; Tsuyoshi Inaba; Ryoji Fukushima (Surgical Case Reports)
Abstract Background Esophageal perforation after aortic replacement/stenting for aortic dissection or aneurysm is a rare but severe complication. However, its cause, standard treatment, and prognosis are unclear. We analyzed the treatment and outcome retrospectively from seven cases experienced at our hospital. Case presentation The median age of the patients was 70 years (range, 41–86), and six of the seven cases were male. As the first treatment, aortic replacement techniques were performed in five, and thoracic endovascular aortic repair (TEVAR) procedure was performed in two. We evaluated the treatment of the perforation, the cause of death, and the median survival time after reparative surgery (esophagectomy). Initial treatment of the perforation was esophagectomy without reconstruction in six and esophagogastric bypass (later, esophagectomy was performed) in one. Three of seven cases could be discharged from hospital or moved to another hospital, but two of these three cases died of major bleeding on postoperative days 320 and 645. The other four esophagectomy cases died in hospital because of sepsis on postoperative days 14, 30, and 41 and major bleeding on postoperative day 54. The one surviving case was a 65-year-old man who underwent reconstruction, and was still alive without signs of infection at 424 days postoperatively. Conclusion The prognosis of esophageal perforation cases after aortic replacement/stenting for thoracic aortic dissection or aneurysm is poor, though there were some cases with relatively long survival. Therefore, the indication for invasive esophagectomy should be decided carefully. Control of infection including regional infection is essential for successful treatment.